2019
DOI: 10.1039/c9mh00094a
|View full text |Cite
|
Sign up to set email alerts
|

Negative piezoelectric effect in an organic supramolecular ferroelectric

Abstract: A pronounced and tunable negative piezoelectric effect in a family of organic small-molecular ferroelectrics is demonstrated and explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Both the experimental and theoretical results confirm that such giant negative longitudinal piezoelectricity and electrostriction result from the large displacive instability of Cu ions coupled with its reduced lattice dimensionality. The proposed mechanism thus implies the prevalence of negative piezoelectricity in ferroelectrics with low-dimension lattice, as what is indeed emerging in the recent literature [89,90].…”
Section: Negative Piezoelectric Effectsupporting
confidence: 60%
“…Both the experimental and theoretical results confirm that such giant negative longitudinal piezoelectricity and electrostriction result from the large displacive instability of Cu ions coupled with its reduced lattice dimensionality. The proposed mechanism thus implies the prevalence of negative piezoelectricity in ferroelectrics with low-dimension lattice, as what is indeed emerging in the recent literature [89,90].…”
Section: Negative Piezoelectric Effectsupporting
confidence: 60%
“…It can be identified from the nanoswelling formation on P40 nanofibers. Many research groups have also reported similar results. The cause of agglomeration is due to the dispersion limit of BF33BT in PVDF solution, thus, increasing the viscosity of the solution, resulting in nanoswellings. , The average of positive peak values of V oc was found to be 11, 33, 47, 62, and 55 V for PENGs based on PVDF, P10, P20, P30, and P40, respectively (Figure c ). Similarly, the average of positive peak values of I sc was found to be 0.2, 0.6, 0.85, 0.92, and 0.88 μA in the same order (Figure d ).…”
Section: Resultsmentioning
confidence: 53%
“…4 Negative piezoelectricity has also been experimentally demonstrated in ferroelectric polymers 5 and in organic molecular ferroelectric materials. 6 BiTeX (X = Cl, Br, and I) compounds have attracted considerable recent interest as strongly polar quasi-2D materials. The breaking of inversion symmetry results from the layer geometry, in which a central Bi layer is neighbored by a Te layer on one side and a halide layer on the other side, forming a triple layer (TL) as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%